1988
DOI: 10.1007/bf02596099
|View full text |Cite
|
Sign up to set email alerts
|

Health risk appraisal modifies cigarette smoking behavior among college students

Abstract: To assess whether Health Risk Appraisal (HRA), a computer-scored lifestyle analysis questionnaire, can result in significant changes in health behavior, a controlled clinical trial with one-year follow-up was conducted among entering freshmen at an urban state university. Three hundred fifty entering freshmen were each assigned to one of four groups: HRA with feedback, HRA without feedback, initial control, and final control. Twenty-two per cent of the nonsmokers in the no-feedback group, as compared with 5% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is also true when considering aggressive treatment protocols (toxic chemotherapy, organ transplant, or major surgery) for cancer or heart disease. Second, it can motivate patients to modify health behaviors such as adherence to medication, smoking, diet, exercise, and alcohol use by quantifying the impact these changes have on risk and by charting progress after modifying risk 4650 . Third, it can identify patients in need of intensive management either with respect to site of care (outpatient, inpatient, intensive care unit, skilled nursing facility, nursing home) or care management (case management, frequency of follow up).…”
Section: Discussionmentioning
confidence: 99%
“…It is also true when considering aggressive treatment protocols (toxic chemotherapy, organ transplant, or major surgery) for cancer or heart disease. Second, it can motivate patients to modify health behaviors such as adherence to medication, smoking, diet, exercise, and alcohol use by quantifying the impact these changes have on risk and by charting progress after modifying risk 4650 . Third, it can identify patients in need of intensive management either with respect to site of care (outpatient, inpatient, intensive care unit, skilled nursing facility, nursing home) or care management (case management, frequency of follow up).…”
Section: Discussionmentioning
confidence: 99%
“…Computerized education programs have helped patients improve their health as well as the process through which they receive care. Some examples include computerized health promotion [ 60,61] and educational information in the management of medical condition [62,63]. A recent systematic review of 39 eligible randomized clinical trials found that patient participation in and outcomes of diabetes care can be improved by computerized knowledge management interventions.…”
Section: Computerized Delivery Of Clinical Evidencementioning
confidence: 99%
“…A total of 130 studies were located; only 64 of these studies were controlled trials. These included 47 of the 48 controlled trials from Sussman, Sun, & Dent [ 10 ] (the Moochan study was deleted because it did not include a minimal program control condition), 3 studies from the Grimshaw & Stanton [ 19 ] review that were not contained in the concurrent review [ 21 - 23 ], and 14 additional studies located subsequently to both of these reviews [ 24 - 37 ]. The data used for the present analysis and abbreviated references for these 64 studies are contained in an additional text file [see Additional file 1 ].…”
Section: Description Of the 64 Controlled Studies In The Present Revimentioning
confidence: 99%
“…In addition, we added three new studies to this category. These were: dormitory [ 21 ], shopping mall and home [ 22 ], and worksite [ 34 ].…”
Section: Description Of the 64 Controlled Studies In The Present Revimentioning
confidence: 99%